The Role of ChatGPT in Improving the Efficiency of Business Communication in Management Science - Suryanto Nugroho; Anwar Tonggo Sitorus; Mohammad Habibi; Edy Wihardjo; Muhammad Subhan Iswahyudi (Politeknik Ganesha Medan, 2023)
In the era of globalisation and rapidly growing information technology, business communication has become one of the critical aspects of management science that plays an important role in the success of an organisation. Efficient business communication can lead to better collaboration, faster decision-making, and improve overall organisational productivity and performance. This research aims to investigate in depth about the role of ChatGPT in improving the efficiency of business communication in management science. The current research type is qualitative. Data collection techniques include listening and recording important information to conduct data analysis through data reduction, data display, and conclusion drawing. The study results show that in the ever-evolving era of technology and digitalisation, ChatGPT has proven itself as an effective tool in improving the efficiency of business communication in management science. From improving the responsiveness and availability of communication, data analysis, strategic support, to facilitating collaboration, development, and innovation, ChatGPT provides organisations with a variety of advantages in various aspects of their operations.